The Evolutionary Dynamics of Repetitive DNA and Its Impact on the Genome Diversification in the Genus Sorghum - Kuo, Yi-Tzu; Ishii, Takayoshi; Fuchs, Jörg; Hsieh, Wei-Hsun; Houben, Andreas; Lin, Yann-Rong (Frontiers in Plant Science, 2021)
Polyploidization is an evolutionary event leading to structural changes of the genome(s), particularly allopolyploidization, which combines different genomes of distinct species. The tetraploid species, Sorghum halepense, is assumed an allopolyploid species formed by hybridization between diploid S. bicolor and S. propinquum. The repeat profiles of S. bicolor, S. halepense, and their relatives were compared to elucidate the repeats’ role in shaping their genomes. The repeat frequencies and profiles of the three diploid accessions (S. bicolor, S. bicolor ssp. verticilliflorum, and S. bicolor var. technicum) and two tetraploid accessions (S. halepense) are similar. However, the polymorphic distribution of the subtelomeric satellites preferentially enriched in the tetraploid S. halepense indicates drastic genome rearrangements after the allopolyploidization event. Verified by CENH3 chromatin immunoprecipitation (ChIP)-sequencing and fluorescence in situ hybridization (FISH) analysis the centromeres of S. bicolor are mainly composed of the abundant satellite SorSat137 (CEN38) and diverse CRMs, Athila of Ty3_gypsy and Ty1_copia-SIRE long terminal repeat (LTR) retroelements. A similar centromere composition was found in S. halepense. The potential contribution of S. bicolor in the formation of tetraploid S. halepense is discussed.